PERILAKU SETTLEMENT PADA STRUKTUR GEDUNG REKTORAT UNIVERSITAS PANCA BHAKTI PONTIANAK - yufiansyah, yufiansyah; Parabi, Arif; Widodo, Muji Listyo (Jurnal Teknologi Infrastruktur, 2022)
In the proper category, buildings must stand upright, sturdy and strong for a long period of time and no settlement occurs. Panca Bhakti University (UPB) is currently building campus facilities and infrastructure to meet the growing number of students, one of which is the rectorate building. Before the rectorate building is put into operation, an initial investigation is needed to find out whether or not settlement has occurred in the building structure. Settlement is a decrease in subgrade elevation caused by a layer of soil that is loaded on it, causing the soil beneath to experience an increase in stress. The implementation of the research is by making observations and measuring settlement behavior with a waterpass. The purpose of this investigation is to identify and monitor settlement behavior and determine settlement values ​​that occur in the structure of the Panca Bhakti University rectorate building. The results showed that the highest settlement value occurred at observation points T2-LT.4 and T6-LT.4 with a value of 5 mm. At the observation points T6-LT.1, T1-LT.4, and T3-LT.4 the height difference was 3 mm. While the observation points T1-LT.1, T2-LT.1, T3-LT.1, T4-LT.1, T5-LT.1, T4-LT.4, and T5-LT.4 with a value of 0 , it can be said that there is no difference in height. The average height difference value of all observation points is 1.58 mm. Settlement data is needed so that the risk of structural damage to buildings can be identified early. With this research data, it can be used as a justification for the reliability of the building as well as reference data for monitoring the maintenance of the Panca Bhakti University rectorate building in the future. Keywords: Settlement, observation, building structure